Prosedur Pengembangan Kurikulum PGMI (Mengacu KKNI, SNPT, dan MBKM) - Marvida, Tria; Darmiah, Darmiah (Universitas Indraprasta PGRI Jakarta, 2024)
In line with the demands of an advanced society, the curriculum in higher education needs to continuously evolve to meet these needs. This study aims to analyze the development of higher education curricula based on the Indonesian National Qualifications Framework (KKNI) and the National Standards for Higher Education (SNPT), while also supporting the implementation of the Merdeka Belajar Kampus Merdeka (MBKM) program. The research is descriptive and qualitative, utilizing a literature review approach. Data were collected through document studies of relevant policy documents, curriculum development guidelines, and related literature. The data were analyzed using content analysis techniques. The results indicate that curriculum development follows several stages: (1) formulation of Graduate Competency Standards (SKL), (2) formulation of Graduate Learning Outcomes (CPL), (3) formulation of program graduate profiles, (4) formulation of program learning outcomes, (5) formulation of course learning outcomes, (6) identification of key concepts and keywords in course learning outcomes, and (7) development of the Semester Learning Plan (RPS). The implementation of MBKM requires higher education institutions to provide services that allow students to exercise their learning rights through eight designated programs. The implications of this research show that KKNI- and SNPT-based curriculum development supports the flexibility of higher education and the successful implementation of MBKM, producing graduates who are competent and ready to face global challenges.